It takes a Flywheel to Fly: Kickstarting and Growing the A/B testing Momentum at Scale - Fabijan, Aleksander; Arai, Benjamin; Dmitriev, Pavel; Vermeer, Lukas (2021 47th Euromicro Conference on Software Engineering and Advanced Applications (SEAA), 2021)
Companies run A/B tests to accelerate innovation and make informed data-driven decisions. At Microsoft alone, over twenty thousand A/B tests are ran each year helping decide which features maximize user value. Not all teams and companies succeed in establishing and growing their A/B testing programs. In this paper, we explore multiple-case studies at Microsoft, Outreach, Booking.com, and empirical data collected, and share our learnings for iteratively adopting and growing A/B testing. The main contribution of this paper is the A/B Testing Flywheel. This conceptual model illustrates iteratively navigating the value-investment cycle with the goal to scale A/B testing. In every turn of the flywheel, teams need to invest in order to increase the A/B testing momentum. We describe the investments in software development processes that have been advantageous in getting the flywheel to turn. We also share example metrics that track the progress towards sustainable A/B testing momentum.